2004
DOI: 10.1023/b:pham.0000041466.84653.8c
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Human P-glycoprotein with Simvastatin, Simvastatin Acid, and Atorvastatin

Abstract: The moderate level of P-gp mediated transport and low affinity of SV, SVA, and AVA for P-gp inhibition compared to systemic drug levels suggest that drug interactions due to competition for P-gp transport is unlikely to be a significant factor in adverse drug interactions. Moreover, the inconsistencies between P-gp inhibition studies and P-gp transport of SV, SVA, and AVA indicate that the inhibition studies are not a valid means to identify statins as Pgp substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 23 publications
6
79
1
Order By: Relevance
“…Furthermore, compounds that are actively transported into the bile in vivo may be pumped back into the medium in these static hepatocyte experiments, which would also artificially increase AUC 0-ϱ . Interestingly, a similar underprediction of CL int ub in vivo using the AUC 0-ϱ method was also observed using human hepatocytes (data not shown) for the known PgP substrate atorvastatin (Hochman et al, 2004) and montelukast. This is particularly pertinent because Zhao et al (2005) have demonstrated an efficient PgP-mediated efflux using human hepatocytes.…”
Section: Contribution Of Hepatic Uptake To Clearancesupporting
confidence: 67%
“…Furthermore, compounds that are actively transported into the bile in vivo may be pumped back into the medium in these static hepatocyte experiments, which would also artificially increase AUC 0-ϱ . Interestingly, a similar underprediction of CL int ub in vivo using the AUC 0-ϱ method was also observed using human hepatocytes (data not shown) for the known PgP substrate atorvastatin (Hochman et al, 2004) and montelukast. This is particularly pertinent because Zhao et al (2005) have demonstrated an efficient PgP-mediated efflux using human hepatocytes.…”
Section: Contribution Of Hepatic Uptake To Clearancesupporting
confidence: 67%
“…Indeed, a recent clinical DDI study showed that BOC increased plasma atorvastatin AUC and C max 2.3-and 2.7-fold, respectively (Hulskotte et al, 2011). It is noteworthy that atorvastatin has low intestinal availability [Fa*fg (intestinal availability) = 0.24] (Shitara, 2011) in humans, conceivably due to gut CYP3A4 metabolism and Pgp efflux (Hochman et al, 2004). Therefore, the potential of BOC to inhibit atorvastatin gut metabolism might be an additional contributing factor to the increased systemic exposure of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was recognized that a broad variety of drugs, including many cardiovascular drugs such as statins and angiotensin II-receptor antagonists, is transported through biological membranes via specific transport proteins (15,(22)(23)(24). For example, the efflux transporter Pglycoprotein, which translocates its substrates from the inside of the cell to the outside (e.g., from the hepatocyte into bile) is a major determinant of drug effects (1).…”
Section: Discussionmentioning
confidence: 99%